Detection of Platelet Desensitization in Pregnancy-Induced Hypertension Is Dependent on the Agonist Used - Ahmed, Y; Sullivan, M H F; Elder, M G (Thrombosis and Haemostasis, 1991)
The aggregation of platelets from women with pregnancy-induced hypertension (P.I.H.), or with normal pregnancies, in response to arachidonic acid, ADP, collagen or platelet activating factor (PAF) was examined. No differences in platelet aggregation between the normotensive and hypertensive women were detected when arachidonic acid or collagen were used to stimulate in vitro platelet aggregation. Higher concentrations of ADP and PAF were required to aggregate platelets from women with P.I.H. compared with platelets from normotensive controls. Platelets from women with normotensive pregnancies (n = 80) aggregated maximally in response to 20 nM PAF without exception. Reversible aggregation by platelets from women with P.I.H. (n = 25) was observed at the same concentration of PAF; again, this was found in all subjects tested. These results indicate that PAF at a concentration of 20 nM can clearly demonstrate differences in aggregation of platelets from women with normotensive pregnancy and women with P.I.H.